Pain Characteristics in Patients with Inflammatory Bowel Disease: A Monocentric Cross-Sectional Study. (4th April 2022) - Hardy, Pierre-Yves; Fikri, Jalal; Libbrecht, Dominique; Louis, Edouard; Joris, Jean
Abstract: Background and Aims: The abdominal pain common in inflammatory bowel disease [IBD] patients is traditionally associated with inflammation but may persist during clinical remission. Central sensitization [CS] has not previously been explored in these patients. This study aimed to determine the epidemiology of pain in IBD patients and to specify pain characteristics with particular attention to CS. Methods: This cross-sectional study included 200 patients; 67% had Crohn's disease [CD]. Pain was assessed using the McGill questionnaire, using the Douleur Neuropathique 4 [DN4] questionnaire and by clinical examination. Its impacts on quality of life, depression and anxiety were also assessed. Results: Three-quarters of IBD patients complained of pain, including intermittent pain attacks, 62% reported abdominal pain and 17.5% had CS. The prevalence of pain [83.6% vs 59.1%; p < 0.001] and abdominal pain [68.7% vs 48.5%; p = 0.006] was higher in CD patients than in ulcerative colitis [UC] patients. Multivariate analysis confirmed that age [ p = 0.02], sex [female] [ p = 0.004] and CD [ p = 0.005] were independent risk factors for pain. Pain intensity was greater in the case of CS (6 [5–3] vs 3 [1.5–5], p < 0.003) which significantly impaired quality of life [ p < 0.003] compared with pain without CS. Conclusions: The prevalence of pain was high in IBD patients [≈75%] and higher in CD patients. Significant impacts on quality of life were confirmed. More than 25% of patients with abdominal pain described CS as responsible for more severe pain and worsened quality of life. Trial registration ref: NCT04488146